Extremely Rare Finding of a Chiton (Mollusca, Polyplacophora) in a Rocky Intertidal Habitat in Nova Scotia (Canada) - Julius A. Ellrich; Ricardo A. Scrosati (Diversity)
Chitons are a group of mollusks (polyplacophores) that differ from the mollusks that are most often found on marine rocky shores (bivalves and gastropods). On the Atlantic coast of North America, chitons have been reported in subtidal habitats from Newfoundland (Canada) to New England (USA). Here, we report the finding of Boreochiton ruber at the mid-to-high intertidal zone in a wave-exposed habitat in Nova Scotia (Canada). After surveying various coastal locations across Nova Scotia for 20 years (2004 to 2024), this was the only intertidal chiton we ever found in such habitats, making this an extremely rare occurrence. Rare species may contribute in unique ways to community functioning, making their reports valuable for biodiversity and ecosystem research.